Urban Semiotics of the Historic Kaleici City: Revealing the Impact of Urbanization through the Argo Ship Metaphor - Akiner, Nurdan; Akiner, Muhammed Ernur; Akiner, Ilknur; Kilic, Serkan (Journal of Urban Sociology, 2026)
Urbanization, a prehistoric concept, has evolved to encompass various dynamics influenced by technology, population growth, and lifestyle, significantly affecting a community's cultural heritage. The study uses satellite imagery from Google Earth Pro to assess the impact of urbanization on Kaleiçi, Antalya's historic district, revealing an increase in new constructions and loss of green space since 2004. The study used Matlab-based temporal comparison of satellite imagery to analyze the effects of urbanization in Kaleiçi over 20 years. Roland Barthes, a cultural theorist, encouraged architects and planners to combine semiology with urban theory. Barthes' semiotic theory was applied to the study of Antalya's old city, Kaleiçi, indicating that efforts have been made to conserve Kaleiçi, a city of historical and cultural value, despite changes in its meaning, much as Barthes' metaphor of the Argo ship. Over the last two decades, Kaleiçi has seen a slight (5.6280%) increase in new structures, reflecting the authorities' effective balance between expansion and preservation of the area's distinctive semiotic character. This study contributes to the growing body of knowledge concerning the consequences of urbanization on cultural assets and provides valuable insights for future conservation programs.